1008 Sleep Efficiency Moderates The Relationship Between Beta-Amyloid And Memory Retention. (27th April 2018) - Wilckens, K A; Tudorascu, D; Snitz, B E; Price, J; Aizenstein, H; Lopez, O; Erickson, K; Lopresti, B; Laymon, C; Minhas, D; Mathis, C; Buysse, D; et al.
Abstract: Introduction: Amyloid-β (A β) accumulation is a pathologic hallmark of Alzheimer's disease (AD), although the presence of A β alone may not be sufficient to cause dementia impairments. Modifiable health factors, including sleep, may mitigate functional symptoms of neurodegeneration. Here we assessed whether sleep moderated the relationship between A β and two functional markers of preclinical AD: neuropsychological performance and cerebral glucose metabolism in the parietal cortex. Methods: Participants were 41 older adults (28 cognitively healthy and 13 cognitively impaired) ages 68–100, mean = 86.32. A β was assessed with a global measure of Pittsburgh Compound B (PiB, SUVR 50–70, non-PVC, cerebellum reference). Sleep measures included actigraphically-assessed wake after sleep onset (WASO) and total sleep time (TST). Functional AD markers included neuropsychological performance and cerebral glucose metabolism in the parietal cortex. Neuropsychological performance was assessed with visual memory recall using the Rey-Osterrieth Complex Figure task, cognitive flexibility using the Trail-Making test (TMT-B), and phonemic (FAS) verbal fluency. Hierarchical linear regression models were performed with each neuropsychological measure or parietal glucose metabolism as the dependent variable, and sleep (WASO or TST) and A β and their interaction as the independent variables. Results: WASO significantly moderated the relationship between A β and immediate (β = 0.42, p = 0.01) and delayed memory recall (β = 0.47, p = 0.002, corrected for multiple comparisons): among individuals with higher A β, less WASO was associated with better memory recall. There were no moderating associations for TMT-B or verbal fluency, p 's > 0.30. Lower WASO and longer TST were associated with higher parietal glucose metabolism across all participants, β = -0.34, p = 0.034 and β= 0.36, p = 0.023, respectively. Conclusion: These results support the general hypothesis that sleep relates to functional markers of AD, and specifically suggest that higher sleep efficiency mitigates the association between Aβ and visual memory recall. Future work should evaluate the potential protective role of sleep efficiency in memory impairment and progression of Alzheimer's disease. Support (If Any): NIH: K01 AG049879 (KAW); K01 AG037562 (ADC); P01 AG025204 (WEK); RF1 AG025516 (WEK); P50 AG005133 (OLL).